2022
DOI: 10.3389/fcvm.2022.958316
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon ablation for atrial fibrillation: Effects on neuromodulation

Abstract: Pulmonary vein isolation (PVI) represents the mainstay of atrial fibrillation (AF) ablation, and PVI with cryoballoon catheter (CB) ablation (CB-A) has proven to be as effective and safe as radiofrequency ablation (RF-A). Although AF is initiated by triggers arising from the pulmonary veins (PV) and non-PV foci, the intrinsic cardiac nervous system (ICNS) plays a significant role in the induction and maintenance of AF. The ICNS is an epicardial neural system composed of ganglionated plexi (GPs) and a complex n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The cardiac autonomic nervous system (ANS) is composed of interconnected clusters of autonomic ganglia, known as ganglionated plexi (GP), which have been implicated in the initiation and maintenance of atrial fibrillation (AF) 1,2 . Pulmonary vein isolation (PVI) with thermal ablation, namely radiofrequency and cryoballoon ablation (CB), has been demonstrated to concomitantly affect the surrounding GP, as documented by intraprocedural vagal reactions and postprocedural heart rate (HR) increase 3,4 . Unlike thermal energy sources, pulsed‐field ablation (PFA) is a nonthermal ablative modality characterized by selectivity for the cardiac tissue 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiac autonomic nervous system (ANS) is composed of interconnected clusters of autonomic ganglia, known as ganglionated plexi (GP), which have been implicated in the initiation and maintenance of atrial fibrillation (AF) 1,2 . Pulmonary vein isolation (PVI) with thermal ablation, namely radiofrequency and cryoballoon ablation (CB), has been demonstrated to concomitantly affect the surrounding GP, as documented by intraprocedural vagal reactions and postprocedural heart rate (HR) increase 3,4 . Unlike thermal energy sources, pulsed‐field ablation (PFA) is a nonthermal ablative modality characterized by selectivity for the cardiac tissue 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Pulmonary vein isolation (PVI) with thermal ablation, namely radiofrequency and cryoballoon ablation (CB), has been demonstrated to concomitantly affect the surrounding GP, as documented by intraprocedural vagal reactions and postprocedural heart rate (HR) increase. 3,4 Unlike thermal energy sources, pulsed-field ablation (PFA) is a nonthermal ablative modality characterized by selectivity for the cardiac tissue. [5][6][7] Recent evidence suggested that the Farapulse TM PFA system (Boston Scientific) induces minimal effects on the ANS, compared with thermal singleshot technologies.…”
Section: Introductionmentioning
confidence: 99%